BUILDING A LITERACY CULTURE FROM AN EARLY AGE AT SDN 72 BANDA ACEH - Susianti Susianti (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This article explores the efforts made by SDN 72 Banda Aceh in fostering a culture of literacy among elementary school students from an early age. Recognizing the importance of literacy in personal and academic development, the school has implemented various interactive literacy programs that actively engage students, parents, and the community. This research employs a mixed-methods approach, utilizing both quantitative and qualitative data to assess the impacts of these literacy initiatives on students' reading interests and language skills. The quantitative data were collected through surveys administered to 100 students before and after the implementation of the literacy programs, measuring indicators such as reading interest, frequency of reading, and writing proficiency. The qualitative component involved interviews with teachers and parents, as well as observations of literacy-related activities conducted at the school. The findings indicate a significant increase in students' reading interest—from 40% to 75% reporting high interest—alongside notable improvements in writing skills. The results underscore the effectiveness of SDN 72 Banda Aceh interactive literacy programs and highlight the crucial role of parental and community involvement in cultivating a sustainable culture of literacy. The study concludes with recommendations for the school to further develop and expand its literacy initiatives, reinforcing the collaborative effort needed among schools, families, and communities to nurture lifelong literacy skills in students.